GAMBARAN PENANGANAN KELUHAN PELANGGAN DI UNIT CUSTOMER SERVICE RUMAH SAKIT UMUM DAERAH TUGUREJO SEMARANG - Yonasari, Estie; Arso, Septo Pawelas (Fakultas Kesehatan Masyarakat, 2018)
Services provided by the Hospital will affect patient satisfaction as a customer. Hospital services that are not in accordance with customer expectations, will cause dissatisfaction so that it will make people complain about the services.Â Handling of complaints in several health care institutions, is still considered not optimal enough. The Community Satisfaction Index on the handling of complaints, suggestions and input from Tugurejo Regional General Hospital decreased from 84,657% in 2016 to 73,078% in 2017. The purpose of this study is to describe the handling of customer complaints at the Tugurejo Hospital, Semarang. This research uses descriptive qualitative research design. The results of this study indicate that in the Input section: there is no specific training in handling customer complaints that have been followed by Customer Service officers, there is no specific budget for handling complaints, facilities and infrastructure to support handling complaints are complete, but still require improvement of conditions and management. This hospital also has no SOP for handling complaints in the Customer Service Unit. In part of Process: handling of complaints made by the Customer Service Unit Hospital Tugurejo is respond to, complaint, investigate, resolve, check, complete, compile, deploy and develop. There are still some problem in the process of responding, overcoming, checking and compiling. Output: incoming complaints have been handled well, but there are still some complaints are repeated in the next month and there are some complaints that must be completed to the management level. The indicator of the handling of complaints in the Customer Service Unit is the complaining customer, can receive an answer from the officer and is willing to sign the complaint settlement form. From the results of the identification of the relationship between product / service failure, customer complaints and actions to be taken, the Tugurejo Hospital Customer Service Unit is in Quadrant 2 of Barlow-Moller.Â